Using high magnification to select sperm: a large prospective cohort study comparing ICSI and IMSI. Issue 1 (2020) - Cassuto, Nino Guy; Bouret, Dominique; Hatem, Ghada; Larue, Lionel; Lédée, Nathalie; Ruoso, Lea; Marzouk, Flora; Hazout, André; Tezarik, Jan; Mouzon, Jacques de; Zarca, Kevin; Shulman, Adrian; et al.
No abstract available